Targeted Therapies in Axial Psoriatic Arthritis - Floris, Alberto; Congia, Mattia; Chessa, Elisabetta; Angioni, Maria Maddalena; Piga, Matteo; Cauli, Alberto (Frontiers in Genetics, 2021)
Specific and high-quality evidence on efficacy of the current targeted therapies for axial disease in psoriatic arthritis (axPsA) are still scarce. Indeed, almost all the cohorts investigated in clinical trials on PsA consisted of patients with peripheral arthritis, whose just a small number had also axial involvement. Only one randomized controlled trial was so far specifically designed to assess efficacy of a biological disease modifying anti-rheumatic drug (DMARD) in axPsA. For other biological and synthetic targeted DMARDs the most specific evidence for treatment in axPsA are extrapolated from post-hoc analyses based on PsA patients with concomitant peripheral and axial manifestations. Further, the current trials and post-hoc analysis on axPsA are affected by major limitations, including the lack of a widely accepted definition of axPsA and the lack of specific and validated outcome measures. Finally, poor data are available on genetics of axPsA, although alleles differentially expressed in different patterns of axPsA, might offer advantages in the prospective of a personalized medicine in axPsA patients. Overall, this review suggests that there is an urgent need for more reliable evidence derived from studies specifically designed for axPsA and based on a validated definition of axPsA and on specific outcome measures.